Pembinaan Akidah dan Tasamuh di Sekolah Menengah Atas Bhakti Karya dan Sekolah Menengah atas Harapan Bangsa Kecamatan Kaloran Kabupaten Temanggung - Tri Laksono; Mukh Nursikin (Attractive : Innovative Education Journal, 2024)
This research aims to analysis the development of tasamuh beliefs at Bhakti Karya Kaloran High School and Harapan Bangsa High School Kaloran, the forms of activities that support the development of tasamuh beliefs at Bhakti Karya Kaloran High School and Harapan Bangsa High School Kaloran, supporting factors and factors inhibiting the development of tasamuh faith at SMA Bhakti Karya Kaloran and SMA Harapan Bangsa Kaloran. This research method is qualitative research, the approach used is a case study. The result show that Forms of activities that support the development of tasamuh beliefs at Bhakti Karya Kaloran High School and Harapan Bangsa Kaloran High School, namely Islamic religious lessons, habituation to worship at school, charity activities, commemoration of Islamic holidays. Supporting factors and inhibiting factors in the development of tasamuh faith at Bhakti Karya Kaloran High School and Harapan Bangsa Kaloran High School, namely the role of teachers and teaching staff, a conducive school environment, the inhibiting factors are environmental influences outside the school and the uncontrolled influence of social media. The positive impact on the development of tasamuh faith and morals for students is; foster the principles of religious belief and awareness in a heterogeneous and mutually respectful environment.